Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s00404-018-4885-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of endometrial cancer in asymptomatic postmenopausal patients with thickened endometrium: data from the FAME-Endo study: an observational register study

Abstract: Our data compare favorably to a theoretical cohort suggesting a clinically reasonable cut-off of > 11 mm endometrial thickness to discriminate between "normal" and "pathological". The data regarding "risk for endometrial cancer" can be used for counseling affected women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…While this finding was significant, the confidence interval was wide, reflecting uncertainty. Hefler et al determined the absolute risk of endometrial cancer in a woman without bleeding with endometrial thickness of ≥10 and ≥12 mm to be 5.2% and 6.7%, respectively 14 . However, why 5.2–6.7% is an acceptable absolute risk level for detecting endometrial cancer was not clearly justified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While this finding was significant, the confidence interval was wide, reflecting uncertainty. Hefler et al determined the absolute risk of endometrial cancer in a woman without bleeding with endometrial thickness of ≥10 and ≥12 mm to be 5.2% and 6.7%, respectively 14 . However, why 5.2–6.7% is an acceptable absolute risk level for detecting endometrial cancer was not clearly justified.…”
Section: Resultsmentioning
confidence: 99%
“…Insufficient endometrial sampling occurred in 6.3% (57/900) in Hefler et al 14 risk of patients undergoing an invasive procedure without diagnostic yield. However, there were no insufficient samples reported by Li and Li, 16 Seckin et al, 20 Giannella et al 13 and Ozelci et al 18 Whether there were truly no insufficient samples or whether they were excluded from analyses was not specified.…”
Section: Insufficient Samplementioning
confidence: 98%
See 2 more Smart Citations
“…However, this study had a smaller sample size and therefore did not account for individual risk factors. A larger prospective registered study included a total of 900 women with thickened endometrium 16 . This study reported the risk of atypical EH and EC to be 7.9% when using a cut‐off of 11 mm.…”
Section: Discussionmentioning
confidence: 99%